Factors That Influence the Success of Milk Tea Shops at North Fairview: Basis for Crafting a Development Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Filipinos typically enjoy sipping on refreshing drinks like samalamig and buko juice. However,recently, a new product was developed. Milk tea has become popular in the Philippines. Thisbusiness created distinctively designed drinks to encourage consumers to share pictures oftheir drinks on social media. The popularity of milk tea quickly went viral and attracted a lot ofattention. This study was to evaluate the factors that contribute to the business's success. Thegoal of this study is to ascertain how many variables affect how successful a business is. Thestudy also looks into the possibilities that came their way and the difficulties they faced whileoperating their business.This study exposed that the difference was not significant between the assessment ofadministrator and employee group of respondents in the factors that influence the businesssuccess in terms of vision, mission, goals, and objectives; organizational structure; jobdescriptions and policies; and rules and regulations. This was validated by the t-computedvalue of 5.5, which is greater than the t-critical value of 2.712 at a 0.01 level of significance and38 degrees of freedom. Having these compared values, the null hypothesis was rejected. Theresults showed the difficulties experienced by the two groups of respondents, mainlyineffective management, competitors, out-of-scope work, and dishonesty. However, therespondents undertook the following solutions: Collaborate with the employees to increaseefficiency and productivity; Promote the company's product strength; Enhance knowledge andskills; Establish employment agreements and corporate policies.The proposed development plan can be crafted to enhance the level of business success.This includes the key result area on vision, mission, goals, and objectives; organizationalstructure; job descriptions; and policies, rules, and regulations. Furthermore, the researchersproposed recommendations and development plans to help the administrators andemployees enhance and guide the business to success.
Keywords: Business